A multicomponent coupling strategy for the synthesis of the triene component of the oxazolomycin antibiotics - Bulger, P; Moloney, M; Trippier, P (2002)
Concise and versatile routes suitable for the synthesis of three geometric isomers of an analogue of the left hand triene subunit of oxazolomycin are reported, using a Stille coupling strategy.